1994
DOI: 10.1029/94pa01455
|View full text |Cite
|
Sign up to set email alerts
|

Benthic phosphorus regeneration, net primary production, and ocean anoxia: A model of the coupled marine biogeochemical cycles of carbon and phosphorus

Abstract: We examine the relationships between ocean ventilation, primary production, water column anoxia, and benthic regeneration of phosphorus using a mass balance model of the coupled marine biogeochemical cycles of carbon (C) and phosphorus (P). The elemental cycles are coupled via the Redfield C/P ratio of marine phytoplankton and the C/P ratio of organic matter preserved in marine sediments. The model assumes that on geologic timescales, net primary production in the oceans is limited by the upwelling of dissolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
267
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(282 citation statements)
references
References 75 publications
7
267
2
Order By: Relevance
“…Mass-balance approaches demonstrate that crustal overturn only buffers oxygen over hundreds of millions of years [Van Cappellen and Ingall, 1996]. By enhancing phosphorus input through amplifying rock weathering and suppressing phosphorus output through preferential recycling from sediments, different organisms increase the amount of phosphorus in circulation in the Earth system, while other nitrogen-fixing organisms help maintain nitrogen at equivalent, biologically available levels to phosphate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass-balance approaches demonstrate that crustal overturn only buffers oxygen over hundreds of millions of years [Van Cappellen and Ingall, 1996]. By enhancing phosphorus input through amplifying rock weathering and suppressing phosphorus output through preferential recycling from sediments, different organisms increase the amount of phosphorus in circulation in the Earth system, while other nitrogen-fixing organisms help maintain nitrogen at equivalent, biologically available levels to phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of data relating primary production to sedimentation rate [Miiller and Suess, 1979] and sedimentation rate to organic carbon burial [Henrichs and Reeburgh, 1987], organic carbon burial is assumed to be a quadratic function of new production, given by (3) and independent of ocean anoxia. The nonlinearity implies that increases in new production occur primarily in the shelf environments where a greater fraction of production is preserved than in the deep ocean [Van Cappellen and Ingall, 1994]. A sensitivity study in which the power relating organic carbon burial to changes in new production was altered over the range 1-3 revealed that this does not have a great impact on the final steady state of oxygen [Lenton, 1998b].…”
Section: Basic Ocean Model (M1)mentioning
confidence: 99%
“…Owing to the high energy demand of breaking the molecular nitrogen bond, N 2 -fixation can only occur when fixed-N (nitrate and ammonia) concentrations are low, and nutrient phosphorus is in excess supply (Tyrrell, 1999). This means that fixed-N (nitrate and ammonia) in the surface water most likely had been consumed by intense denitrification and/or anammox processes (Junium and Arthur, 2007;Luo et al, 2011) while phosphorus was efficiently recycled under anoxic conditions (Ingall et al, 1993;Van Cappellen and Ingall, 1994). In the early Cambrian, increasing weathering sulfate flux into the ocean (Feng et al, 2014;Jin et al, 2014) and high TOC (Fig.…”
Section: Cambrian Stagementioning
confidence: 99%
“…Sedimentation rates of organic matter vary spatially, especially in the archipelagos because of the fractured topography (Winterhalter et al 1981) and temporally because of the seasonality of plankton growth and senescence (Bianchi et al 2002). Anoxia which is common in the Baltic Sea can favour burial of organic matter but diminish the burial of P because the formation of Fe-oxyhydroxides that bind PO 4 is inhibited (Van Cappellen and Ingall 1994;Ingall et al 1993;Mort et al 2010;Jilbert et al 2011). In the Baltic Sea, Edlund and Carman (2001) reported higher organic C:P ratios for anoxic than for oxic sites and Jilbert et al (2011) suggested increasing rates of P mineralisation in more reduced conditions.…”
Section: Current Process Understandingmentioning
confidence: 99%